Analysis of ball speed and accuracy of groundstrokes on a clay court in young tennis players - Nur Ikhwan bin Mohamad (Tanjung Malim, 2024)
Analysis of ball speed and accuracy of groundstrokes on a clay court in young tennis players by Nur Ikhwan bin Mohamad